Contract Agreement in the Islamic Fiqeh - Ziad Shafiq Hasan Qrarya (My University, 2004)
In this study, the researcher deals with rules of contract agreement in the Islamic Fiqeh, and a comparative study with what has been stated in the civil law especially with those laws depending on the Islamic Fiqeh as it is the case of the Jordanian Civil Law. This study includes an introduction, five chapters and a conclusion. The study clarifies the facts and the reality of contract agreement in the Islamic Fiqeh and law. And so as to be plainly defined, the researcher pointed out its distinctiveness, compared it with similar contract agreements and clarified its chief characteristics which make it appears as an independent contract agreement. This study clarifies the importance of contract agreement and its effect in activating the economic cycle, its conditions and implications with their religious evidence from the Kuran, Al-Sunnah and logic. Then the researcher started to explore the elements of the contract agreement which are: the statement, both contractors, and the thing that contracted upon. The researcher also mentioned the reasons in order to cover the legal dimension in his research with an explanation for each element of these points. The researcher prefers to talk about the effects of the contract agreement through indication to the contractor and employer commitment. And in the last chapter, the researcher handles the causes of abolishing the contract agreement in both Al-Sharee'ah rules and law. An index of the Kuranic verses, prophetic traditions, biographies of the famous figures, references and sources is added at the end of this study.

تناولت الرسالة موضوع " عقد المقاولة في الفقه الإسلامي " دراسة مقارنة أوضحت في مقدمتها – التي تحتوي خمسة فصول وملا حقها – مدى قدرة الفقه الإسلامي على استيعاب المستجدات، ومنها عقد المقاولة وغيره من العقود، بغرض رفع الحرج عن الناس وتيسير أمور حياتهم. ومهدت للدراسة بتعريف العقد لغة وفقها وقانونا ، ثم انتقلت للحديث عن حقيقة عقد المقاولة، وأهم خصائصه التي يمتاز بها عن غيره، والتي اعتمد ت عليها لتمييزه عن سائر العقود ، وانتهى البحث إلى أن عقد المقاولة عقد مستقل عن غيره، وإن شاركه في بعض صفاته. وعالجت الدراسة في فصلها الثاني ما لعقد المقاولة من أثر في تنشيط الحركة الاقتصادية ، بجميع صوره، سواء قدم المقاول العمل والمادة الخام من عنده، وهذه صورة عقد الاستصناع، أو قدم العمل وحده، والتي تعد من قبيل الأجير المشترك، ومن خلال ذلك توصلت إلى أدلة مشروعية عقد المقاولة من القرآن و من السنة والمعقول. وعالجت الدراسة في الفصل الثالث مقومات عقد المقاولة، وما ينبغي أن يتوافر في كل ركن من شروط، كما هو الحال في عقد البيع والإجارة وسائر العقود. وتناول الفصل الرابع الآثار التي يخلفها عقد المقاولة من التزامات في حق كل من المقاول وصاحب العمل، وما يتبعها من مسائل كالشرط الجزائي، وحكم التعديلات والإضافات. وأما الفصل الخامس فقد عالجت الدراسة فيه أسباب انقضاء عقد المقاولة في كل من الشريعة والقانون، على غرار ما تنتهي به الإجارة في الفقه الحنفي. وتضمنت الخاتمة أهم النتائج التي توصلت إليها الدراسة، وإلحاق الفهارس بها، وهي فهارس الآيات القرآنية الكريمة، والأحاديث النبوية الشريفة، والأعلام، والمصادر والمراجع.
عقد المقاولة في الفقه الإسلامي وما يقابله في القانون المدني